Best of Jughead : crowning achievements - Goldwater, John L.; Montana, Bob.; Root, Tom.; Lindsey, Rex,; Ruiz, Fernando, (Archie & friends all-stars ;, 2011)
Collects the adventures of Jughead, Archie, and the rest of the gang from Riverdale High.